Community development practice in Africa : putting theory into practice - Gyan, Charles; Kreitzer, Linda, 1955-; Ouedraogo, Somnoma Valerie (Emerald Publishing Limited : Information Age Publishing Inc., 2024)
"This project seeks to broaden the theoretical and practical understandings of community development by investigating community development through an African lens. Whereas most of the community development books used by professors in Africa are mostly focused on community development in the global north, there is a need to develop, collect, and promote scholarship on community development practices that are more transnational and reflective of the realities in the African context. This edited volume therefore seeks to expand our global understanding of community development by exploring the specific forms community development in African contexts, the implications of African community development practice for theories and models of community development, and how such theory is integrated into practice within local African communities. The motivating goal of this edited book is to provide a space to examine the specific contextual factors that impact the history, theory and practice of community development in Africa. Community development should reflect the local context in which it is practiced. This collection is the first to compile and present diverse African perspectives on community development. The contributions included in this edited book will provide a valuable resource for professors, researchers, and practitioners, presenting a range of historically, culturally, and socially situated critical perspectives. In summary, this collection seeks to highlight African context specific literature in the field of community development"-- Provided by publisher.
Keywords: Community development -- Africa, Sub-Saharan.; Political Science -- World -- African.; Relating to migrant groups, diaspora communities or peoples.; Politics and government.; Africa.; elektronické knihy; electronic books